Troubleshooting of filamentous bulking using hybdrid systems - Matos, M. (2010)
The present work aims to evaluate filamentous bulking control in hybrid systems. For this study, four sequencing batch reactors (SBR) fed with acetate were operated without (SBR1) and with support for biofilm growth [5 % (SBR2), 10 % (SBR3) and 20 % (SBR4) of the reactor volume]. The results demonstrated an overabundance of a filamentous fungi-like microorganism in the SBR operating just with suspended biomass. The incorporation of an optimized amount of support for biofilm growth (10 % and 20 %) seemed to suppress the overgrowth of this filamentous microorganism probably due to the combined effect of a decreased biomass loading rate and the physical cut or breakdown of filaments induced by support-to-support collisions.